Melek Bahasa Arab Sehari-hari Calon Jamaah Haji dan Umroh Desa Blembem - Rohman, Nabila Husna Maulida; Fadly, Wirawan (PISCES : Proceeding of Integrative Science Education Seminar; Vol 1 No 1 (2021): 1st AVES & LASER 2021, 2021)
The amount of free time to fill before the departure of prospective Hajj and Umrah pilgrims can be utilized by participating in training which will later support departure as provisions in the holy land. The lack of Arabic language that is taught during rituals is even rare because it is always guided by the Hajj guide. The purpose of the guidance training program held is as a very useful provision because there are still many prospective pilgrims who have minimal understanding of Arabic. This guidance training will also have a good impact on villages that hold guidance training like this because it is still rare to implement Arabic language guidance training for prospective pilgrims for Hajj or Umrah. In this guidance training, 5 stages are carried out when implemented in the field, namely inculturation (introductions), discovery (disclosing information), design (knowing assets and identifying opportunities), define (supporting the implementation of work programs), and reflection (reflection). The results of this guidance training participants feel motivated seen from the results of the questionnaire given the categories of attention, relevance, confidence, and satisfaction which have the same value in each category, namely good. This program will continue to run regularly which will later be opened to be followed by the general public and will become a unique icon in Blembem Village because it provides training and guidance which is rarely held by other villages.